Design process applied for fashion show creation and assembly (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2021)
The fashion show consists of a type of spectacle associated with a variety of elements involved, which has various intentions, as well as the intention to attract the viewer’s desire for consumption. It represents a challenge that goes far beyond creating the pieces in a collection, as it reveals the culture of fashion through a form of art display. Some limitations, such as the typology of space, reduced time for assembly and disassembly, among others, are found during the organization of a fashion show, which end up promoting the need for creative practices to get around them. The purpose of this article is to present the design process applied from the creation to the assembly of a fashion show experienced by the Light e Scene Laboratory (LALUCE), a laboratory linked to the Federal University of Goiás, UFG, where its basic principle is bring architecture, design and art direction students into an approach to scenography in a practical/applied way before they even enter the job market. The work was developed for the FAV Fashion 2018 fashion show, en event held annually by the Fashion Design course at the Federal University of Goiás, which aims to show the course completion works of the students to the university community, family members and fashion professionals. During the process of construction of the parade, several limitations were felt, this way this article will expose the solutions adopted in face of the difficulties and limitations found to guarantee the quality of the proposed parade.